1961
DOI: 10.1063/1.2000413
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Process of a Helical Spin Configuration

Abstract: The behavior of a helical spin configuration of a hexagonal crystal in an applied field is discussed for the case where the axis of the helix is identical with the hexagonal c axis and the magnetization vector in each layer is parallel to the basal plane. In a small field applied parallel to the basal plane, a slight deformation of the helix occurs resulting in a small increase in over-all magnetization. If the field surpasses a certain critical value, the helix changes abruptly into a state with high resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 4 publications
4
36
0
Order By: Relevance
“…Yet, it has been shown that spiral magnetic structures can result from isotropic-exchange interactions if the exchange integrals, between ions in the nn planes and the nnn planes, have certain ratios 23,24 ; these structures can require high applied fields (comparable to or larger than the exchange) to reach magnetic saturation, as is actually observed in the present case. It has been shown for Eu 9 that exchange interactions extend over large distances, so that coupling to nnn planes (and beyond) should be important.…”
Section: A First-order Transitionsupporting
confidence: 57%
“…Yet, it has been shown that spiral magnetic structures can result from isotropic-exchange interactions if the exchange integrals, between ions in the nn planes and the nnn planes, have certain ratios 23,24 ; these structures can require high applied fields (comparable to or larger than the exchange) to reach magnetic saturation, as is actually observed in the present case. It has been shown for Eu 9 that exchange interactions extend over large distances, so that coupling to nnn planes (and beyond) should be important.…”
Section: A First-order Transitionsupporting
confidence: 57%
“…In this model, the spiral state is stable when J 1 = 0, J 2 > 0, and |J 1 | < 4|J 2 | [16]. The validity of applying this model to MnAu 2 was confirmed using density functional theory (DFT) calculations [18,19].…”
Section: Introductionmentioning
confidence: 73%
“…For example, for the helix and fan structures in the continuum limit kd → 0 discussed above that was studied in 1961 [12], the µ xave (H x ) was not presented. However, this can be obtained by averaging cos[φ(z/λ)] for that structure over one wavelength λ for each value of H x /H c .…”
Section: Introductionmentioning
confidence: 99%